Gas de agujeros negros cosmológicos - Gutiérrez, Eduardo Mario (2018)
Black holes with a cosmological origin, the so-called primordial black holes, might have formed in the early Universe from different mechanisms. In this work, we investigate the cosmic evolution of the early Universe inserting a primordial black hole component which interact with the cosmic plasma. Considering extended mass functions, in particular power-law distributions, we find scenarios where the cosmic evolution results different from the standard radiation dominated one.